PIP2 and PIP3 interact with N-terminus region of TRPM4 channel - Bousova, Kristyna; Jirku, Michaela; Bumba, Ladislav; Bednarova, Lucie; Sulc, Miroslav; Franek, Miloslav; Vyklicky, Ladislav; Vondrasek, Jiri; Teisinger, Jan (Biophysical chemistry, 2015)
The transient receptor potential melastatin 4 (TRPM4) is a calcium-activated non-selective ion channel broadly expressed in a variety of tissues. Receptor has been identified as a crucial modulator of numerous calcium dependent mechanisms in the cell such as immune response, cardiac conduction, neurotransmission and insulin secretion. It is known that phosphoinositide lipids (PIPs) play a unique role in the regulation of TRP channel function. However the molecular mechanism of this process is still unknown. We characterized the binding site of PIP2 and its structural analogue PIP3 in the E733-W772 proximal region of the TRPM4 N-terminus via biophysical and molecular modeling methods. The specific positions R755 and R767 in this domain were identified as being important for interactions with PIP2/PIP3 ligands. Their mutations caused a partial loss of PIP2/PIP3 binding specificity. The interaction of PIP3 with TRPM4 channels has never been described before. These findings provide new insight into the ligand binding domains of the TRPM4 channel.
Keywords: vazba proteinů; Molecular modeling; sekvence aminokyselin; Surface plasmon resonance; lidé; dimyristoylfosfatidylcholin; Protein Binding; Phosphatidylinositol 4,5-Diphosphate; Molecular Docking Simulation; simulace molekulového dockingu; Humans; TRPM Cation Channels; peptidové fragmenty; Circular dichroism; sekundární struktura proteinů; fosfatidylinositol-4,5-difosfát; Binding site; Protein Structure, Secondary; Peptide Fragments; molekulární sekvence - údaje; Molecular Sequence Data; kationtové kanály TRPM; Dimyristoylphosphatidylcholine; Amino Acid Sequence; TRPM4 channel; PIP2